2021
DOI: 10.31234/osf.io/w54nt
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the cowl make the monk? The effect of military and Red Cross uniforms on empathy for pain, sense of agency and moral behaviors

Abstract: The present study investigated to what extent the clothes we wear influence prosocial behaviors and two related neuro-cognitive processes, namely the sense of agency and empathy for pain. We tested forty participants wearing civilian, military and Red Cross uniforms across three consecutive days. Participants were tested by pairs and were assigned either to the role of the agent or to the role of the ‘victim’. Agents could deliver real electric shocks to the ‘victim’ in exchange for +€0.05, either following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Giving orders to an entity that does not have its own individual responsibility is likely to prevent a diffusion of the responsibility phenomenon ( Bandura, 2006 ). This effect was more reliable over the P3 than over the eLPP and the lLPP, which is consistent with former studies ( Galang et al, 2021 ; Pech and Caspar, 2021 ). To investigate further which areas mediate this difference, we performed source reconstruction on our EEG data, which revealed the involvement of insula and ACC, as we had initially hypothesized.…”
Section: Discussionsupporting
confidence: 93%
“…Giving orders to an entity that does not have its own individual responsibility is likely to prevent a diffusion of the responsibility phenomenon ( Bandura, 2006 ). This effect was more reliable over the P3 than over the eLPP and the lLPP, which is consistent with former studies ( Galang et al, 2021 ; Pech and Caspar, 2021 ). To investigate further which areas mediate this difference, we performed source reconstruction on our EEG data, which revealed the involvement of insula and ACC, as we had initially hypothesized.…”
Section: Discussionsupporting
confidence: 93%
“…Mendoza and Parks-Stamm (2020) examined the effect of embodying the role of a police officer by wearing a uniform, and found participants in uniform were more likely to shoot unarmed targets on a reaction-time measure (the Shooter Task). Pech and Caspar (2021) investigating the effect of civilian, military and Red Cross uniforms on cognitive and psychological processes. They found that wearing a Red Cross uniform increased empathy for others' pain; civilian clothing led to them administering less shocks themselves; and military uniform increased the sense of participant agency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…insula, inferior frontal gyrus, inferior parietal lobule) and guilt (i.e. anterior cingulate cortex, temporo-parietal junction, putamen and caudate) 11,12 . Other studies have extended these findings by demonstrating that following orders, as opposed to acting freely, induces a reduced implicit sense of agency and a diminished explicit feeling of responsibility.…”
Section: Introductionmentioning
confidence: 99%